Study and Analysis of Removing the Carbon Deposition on the Inner Surface of a Turbo-Shaft by Chemically Assisted Magnetic Grinding - Xu, Hui; Kang, Renke; Zhu, Xianglong; Liu, Lijuan; Wang, Leilei; Chen, Yan (Frontiers in Materials, 2020)
Removing carbon deposition (CD) has always been a challenging problem. On the inner surface of a turbo shaft, CD is observed by scanning electron microscopy (SEM) to analyze its microstructure and composition, and its formation mechanism is analyzed by X-ray diffraction (XRD), infrared spectroscopy, and Raman spectroscopy. Considering the physical and chemical properties of deposited carbon, chemically assisted magnetic grinding (CAMG) is proposed and tested by a translational permanent magnet grinding device. By analyzing the removing mechanism of CAMG, response surface analysis is adopted to analyze the influence law of surface roughness based on the interactions between pairs of the three following parameters: the rotational speed of the rotating magnetic field, needle type, and grinding time. The optimal process parameters can be obtained with a rotational speed of the rotating magnetic field of 600 r/min, a needle type of Φ 1.0 × 5 mm, and a grinding time of 60 min. The surface quality of the workpiece processed by CAMG can be comprehensively appraised by observing the microstructure, calculating the carbon deposit removal ratio and testing the surface stress. Compared to single magnetic grinding, CAMG is more environmentally friendly and has a higher removal ratio and better surface quality with an obvious decrease in residual stress. By professional tests, the remaining deposited carbon is less than the specified value required by the technology, which satisfies the requirements of enterprises.